Octopus Endograft Technique to Treat a Ruptured Thoracoabdominal Aortic Aneurysm. (April 2018) - Li, Zilun; Yin, Henghui; Wang, Mian; Wu, Ridong; Liu, Chenshu; Yao, Chen; Chang, Guangqi
Purpose: To report the use of the octopus endograft technique to treat a patient with a ruptured thoracoabdominal aortic aneurysm (TAAA).Case Report: A 46-year-old man was diagnosed with a contained rupture of a 9-cm type V TAAA. The presence of an occluded superior mesenteric artery (SMA), a stenotic celiac trunk, an enlarged inferior mesenteric artery (IMA), and rich collaterals with the SMA and celiac trunk made endovascular repair with the octopus endograft technique appear feasible. Two stent-grafts were overlapped in the thoracic aorta with the short limb of the distal bifurcated stent-graft about 3 cm above the celiac trunk and the long limb at the level of the renal arteries. A limb graft was introduced into the long limb of the bifurcated stent-graft and deployed with the lower end just above the orifice of the IMA. The celiac trunk was embolized. Viabahn stent-grafts were deployed through the bifurcated stent-graft limbs to revascularize the renal arteries. Completion angiography suggested free flow in the renal arteries, though the gutters around the Viabahn stent-grafts generated a moderate endoleak that persisted at 4-month follow-up. The gutters were then sealed with coil embolization, which eliminated the endoleak and induced complete thrombosis in the aneurysm sac at the 6-month follow-up. One-year computed tomography revealed significant sac shrinkage.Conclusion: The octopus endograft technique may serve as a feasible, effective, and safe treatment alternative for highly selected patients with ruptured TAAA.